The effects of dietary oregano essential oil on live performance, carcass yield, serum immunoglobulin G level, and oocyst count in broilers - Alp, M.; Midilli, M.; Kocabagh, N.; Yilmaz, H; Turan, N.; Gargili, A.; Acar, N.
The present study was designed to evaluate the effect of dietary oregano essential oil on the live performance, carcass yield, and serum IgG levels of broilers and to examine its anticoccidial effect. In a completely randomized design, 1,200 straight-run Ross 308 broilers were allocated into 3 experimental groups, each consisting of 5 replicates. The first group received a basal diet with an anticoccidial (Cygro)at a level of 100 mg/kg of the feed. The second group received diets supplemented with oregano essential oil (Orego-Stim)at a level of 300 mg/kg of the feed, whereas the third group received neither the coccidiostat nor oregano oil (negative control). Throughout the experimental period of 42 d, individual BW and pen feed intake were recorded weekly, and FCR were calculated. Blood samples were collected on d 1 and 42 to determine serum IgG levels. Oocyst counts were determined in excreta samples taken at 10-d intervals from each replication. Results indicated that dietary oregano essential oil and anticoccidial supplementation improved the FCR significantly (P < 0.05)from 21 to 42 d and 1 to 42 d of age, respectively, compared with the negative control diet. Birds fed the oregano oil diet consumed significantly less feed compared with those fed the negative control diet from 21 to 42 d and from 1 to 42 d of age. No dietary effect was observed on the preslaughter weight, carcass yield, or serum IgG level (P > 0.05)at 42 d. Although not significant, there was a slight increase in the serum IgG levels of broilers fed the oregano oil diet. Although the dietary oregano oil significantly (P < 0.05)lowered the excreta oocyst counts compared with those of birds fed the negative control diet, its anticoccidial effect was significantly less than the effects in birds fed the diet with the anticoccidial. In conclusion, oregano essential oil may provide an alternative to conventional anticoccidial additives in broiler feeds
Keywords: BROILER; COCCIDIOSIS; GROWTH PERFORMANCE; OREGANO ESSENTIAL OIL; SERUM IMMUNOGLOBULIN